The biology of the first 1000 days - Kraemer, Klaus; J. Green, Tim; D. Karakochuk, Crystal; C. Whitfield, Kyly (Oxidative stress and disease, 2018)
The first 1,000 days, from conception to 2 years of age, is a critical window of growth and development. Exposures to dietary, environmental, hormonal, and other stressors during this period have been associated with an increased risk of adverse health outcomes. Researchers using cell culture, animal models, and humans have identified this time as a period of rapid physiological change and plasticity with significant potential for lasting effects. As such, interventions during the first 1,000 days will have the greatest impact on outcomes, particularly in low- and middle-income countries where the need is greatest. To date, there is no single resource that compiles our knowledge of the biology of the first 1,000 days. Our knowledge and understanding of the biology behind the first 1,000 days is still limited. This greater understanding is helping us inform effective nutrition policy and programming. The strength of this book lies in its cross- disciplinary nature that encompasses the full range of human biology, providing a more holistic perspective during this critical time frame. Moreover, we have broadened the scope and included important periods before and after the 1,000 days. We have designed this book as a comprehensive resource for those involved in global health and nutrition policy, strategy, programming, or research. This book will also be a resource for students learning about nutrition and health across the 1,000 days. The book includes an exceptional group of contributors who are experts in their given fields. As biology underlies the core of each discussion, it allows the readers to answer the what and why, and, we hope, the how for new discovery research and more effective interventions. Each chapter in this volume provides insight into a specific life stage, disease state, nutrient, and stressor in the first 1,000 days. As such, each chapter can be read independently, providing a comprehensive overview of that subject. However, there is continuity between chapters allowing this collection of chapters to be read cover to cover. The first chapters set the stage, providing a succinct resource to understand the well-established biological mechanisms that underlie growth regulation and nutrient recommendations throughout the first 1,000 days. The next chapters move on to the evidence behind nutrition-specific and nutrition-sensitive interventions to combat adverse outcomes and disease states in the first 1,000 days. This book also features emerging research areas, such as the gut microbiome, environmental enteric dysfunction, and the role of epigenetics in health and development. The final chapter pushes the boundaries of discovery research, exploring novel areas such as proteomics and metabolomics, and how insults such as environmental enteric dysfunction affect metabolism in the first 1,000 days. We approached this book with the ambition to shed more light on the biology during 1,000 days, but there was also a need to put the biology into a broader context of nutrition and health. There are still many gaps in our understanding of the biology of the first 1,000 days. It is only by bridging this knowledge gap through research that we can inform effective interventions to improve outcomes during the first 1,000 days.